Effect of high temperature chemical etching on surface roughness of tungsten carbide substrate - Sudin, Izman; Mohd. Yusof, Noordin; Safari, Habib; Engku Abu Bakar, Engku Mohd Nazim; Aluwi Shakir, Noor Adila; Konneh, Mohamed (2010)
High hardness, lower thermal expansion and friction coefficient, chemical inertness and strength are the most important characteristics of cutting tools, which can be enhanced by coating the tool surface with a thin layer of diamond. A variety of surface pretreatment methods have been developed to enhance diamond nucleation rate density and adhesion strength between diamond films and substrates which include scratching, seeding, electrical biasing, pulsed laser irradiation, interlayer, ion implantation, carburization and chemical pretreatment. Among them, chemical pretreatment is the simplest and cheapest. In this paper, a single step chemical pretreatment using mixture of sulfuric acid and hydrogen peroxide solutions were carried out on tungsten carbide with 6% cobalt (WC-6% Co). Three independent variables such as concentration of sulfuric acid, etching temperature and time were varied to investigate the best combination of these parameters for roughening the WC-6% Co surface. It was found that the highest surface roughness (Ra=1.3μm) was obtained when using 95% concentration of sulfuric acid, and lower etching temperature of 40oC in duration of two minutes etching time.